Government policy and the challenge of eradicating human trafficking in Malaysia - Suhana Saad; Ali Salman (Faculty of Social Sciences and Humanities, UKM,Bangi, 2014)
Malaysia is a destination, and simultaneously, though to a lesser extent, a source and transit country for women and children subjected to human trafficking activities, in particular, those that pertain to forced prostitution and forced labour. Malaysia was placed on Tier 2 of the Watch List of the U.S Department of State’s Trafficking in Persons Report for a second consecutive year in 2011. This was for not fully complying with the Trafficking Victims Protection Act’s minimum standards for the elimination of trafficking although it did make significant efforts to comply with those standards. This study identifies the causes of Malaysia’s human trafficking and examines the reasons why the government has not been entirely successful in addressing human trafficking problem in this country. The study employs qualitative data by interviewing victims at a detention camp known as Rumah Perlindungan 5, Kuala Lumpur. Interviews were also conducted with the Council for Anti-Trafficking in Persons and Anti-Smuggling of Migrants (MAPO) which was established under the Anti-Trafficking in Persons Act 2007 and enforced since February 2008 and amended in 2010 to also include the smuggling of migrants. The findings revealed that the root cause of the government’s lack of success in curbing and eradicating human trafficking has much to do with the fact that trafficking agents or syndicates were able to operate under the guise of legitimate employment agencies, and that there are restrictions such as border problems hampering proper and adequate monitoring of certain strategic and crucial sites. It was also found that the government’s use of conventional media to educate the masses on the dangers of human trafficking has not been very effective in delivering the desired results, thus pointing the way for the use of new media - social media in particular - to complement the public education effort.